2001
DOI: 10.1016/s0304-4203(01)00049-4
|View full text |Cite
|
Sign up to set email alerts
|

Organic pollutants in sea-surface microlayer and aerosol in the coastal environment of Leghorn—(Tyrrhenian Sea)

Abstract: The levels of dissolved and particle-associated n-alkanes, alkylbenzenes, phthalates, PAHs, anionic surfactants and Ž . Ž . Ž . surfactant fluorescent organic matter SFOM were measured in sea-surface microlayer SML and sub-surface water SSL samples collected in the Leghorn marine environment in September and October 1999.Nine stations, located in the Leghorn harbour and at increasing distances from the Port, were sampled three times on the same day. At all the stations, SML concentrations of the selected organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(109 citation statements)
references
References 56 publications
4
103
2
Order By: Relevance
“…3b). By contrast, an evident preferential accumulation in sea-surface microlayer waters is observed for the Ôpartic-ulateÕ phase, despite the fact that EF values are lower than those reported by other authors (Cincinelli et al, 2001;Liu and Dickhut, 1997). It is useful to notice that at station 1 the highest EF for both ÔdissolvedÕ and ÔparticulateÕ phases are relative to samples collected when sun irradiation was lowest, probably related to the reduced photo-degradation that may occur in the sea-surface microlayer (Schroeder and Lane, 1988); however no particular seasonal trend can be deduced.…”
Section: Sea-surface Microlayer Enrichmentcontrasting
confidence: 86%
See 2 more Smart Citations
“…3b). By contrast, an evident preferential accumulation in sea-surface microlayer waters is observed for the Ôpartic-ulateÕ phase, despite the fact that EF values are lower than those reported by other authors (Cincinelli et al, 2001;Liu and Dickhut, 1997). It is useful to notice that at station 1 the highest EF for both ÔdissolvedÕ and ÔparticulateÕ phases are relative to samples collected when sun irradiation was lowest, probably related to the reduced photo-degradation that may occur in the sea-surface microlayer (Schroeder and Lane, 1988); however no particular seasonal trend can be deduced.…”
Section: Sea-surface Microlayer Enrichmentcontrasting
confidence: 86%
“…Despite the fact that important industrial and urban districts are located near the sampling sites, the PAH concentrations found in the sea-surface microlayer waters of the Venice Lagoon are lower than the values found in other coastal areas: at Livorno (Tyrrhenian Sea, Italy) Cincinelli et al (2001) report total concentrations ranging from 1.8 lg/l to 157 lg/l; on the Alexandria coast (Egypt) the mean concentration was 245 ng/l (El Nemr and Abd-Allah, 2003) while at Winyah Bay and North Inlet (South Carolina) it was 650 ± 1200 ng/l (Kucklick and Bidleman, 1994). The PAH concentrations found in this study are also lower than those reported by Cleary et al (2000) for sea-surface microlayer samples collected in 1993 close to the island of Venice, which ranged from 7.18 lg/l to 10.416 lg/l.…”
Section: Sea-surface Microlayer Watersmentioning
confidence: 66%
See 1 more Smart Citation
“…SML and SSL samples were collected under calm sea conditions, by Multi-Use Microlayer Sampler (MUMS), 8,26 which is based on the method proposed by Harvey. 27 Briefly, the sampler consisted in a radio-controlled catamaran, with a Pyrex glass rotating drum (315 mm diameter, 500 mm length, 6 rpm speed).…”
Section: Experimental Sampling Sitesmentioning
confidence: 99%
“…Fractions I and III were analysed on a Varian 4290 gas chromatograph-mass spectrometer (GC-MS), according to a procedure and a temperature program described elsewhere. 8 Separation and identification of the investigated PAHs (FL, PHE, ANT, FLT, PY, BaA, CHRY, BbF, BkF, BaP, DBA, BghiP and IP) were achieved according to Cincinelli et al, 8 by using a Shimadzu (Milan, Italy) HPLC system equipped with two LC-10ADvp pumps, a photodiode array detector SDP M10AVP and a spectrofluorometric detector RF-551.…”
Section: Extraction Of Organic Compoundsmentioning
confidence: 99%